Enhancing the Effectiveness of Public Spending in Norway - Joumard, Isabelle (OECD Economics Department Working Papers, 2002)
Public spending is very high in Norway, partly reflecting an extensive coverage of the welfare system and ambitious regional development objectives. Moreover, several institutional features contribute to dampening the cost-effectiveness of many public-spending programmes. Abundant oil revenues have so far mitigated strains on public finance. However, coping with the depletion of oil resources and the fiscal consequences of ageing would require to increase the cost-effectiveness of many public spending programmes, while leaving some room to cut the high tax-to-GDP ratio. This paper identifies the main sources of inefficiencies and suggests policy options. These include: supplementing the existing deficit rule by an expenditure rule; increasing flexibility in public sector wages and job tenure; reforming the funding system of local governments; raising the contestability of public service provision; intensifying the use of price signals and improving incentives to reduce the ...